2011
DOI: 10.1245/s10434-010-1458-5
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Risk Factors and Clinicopathologic Features for Intrahepatic Cholangiocarcinoma in Southern China: A Possible Role of Hepatitis B Virus

Abstract: The independent association of HBV infection with ICC, synergy between cirrhosis and HBV infection, and some clinicopathological similarities between HBV-related ICC and hepatocellular carcinoma suggests that both may share similar or common tumorigenic process and may possibly originate from malignant transformation of hepatic progenitor cell.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
87
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(91 citation statements)
references
References 44 publications
1
87
0
3
Order By: Relevance
“…The findings of this study suggested that ICC associated with cirrhosis may display a biological behavior similar to that of HCC and, thus, have a better prognosis. Although the etiology of ICC remains unclear, there is growing evidence suggesting that ICC associated with cirrhosis may be derived from the same hepatic progenitor cells as HCC (13,14,18,19) and, thus, behaves more like HCC, which is generally considered to have a more favorable prognosis compared with ICC (2,5,27,29). The observations of the present study indicate that ICC occurring in patients with cirrhosis may share a common carcinogenic process with HCC.…”
Section: ------------------------------------------------------------mentioning
confidence: 48%
See 3 more Smart Citations
“…The findings of this study suggested that ICC associated with cirrhosis may display a biological behavior similar to that of HCC and, thus, have a better prognosis. Although the etiology of ICC remains unclear, there is growing evidence suggesting that ICC associated with cirrhosis may be derived from the same hepatic progenitor cells as HCC (13,14,18,19) and, thus, behaves more like HCC, which is generally considered to have a more favorable prognosis compared with ICC (2,5,27,29). The observations of the present study indicate that ICC occurring in patients with cirrhosis may share a common carcinogenic process with HCC.…”
Section: ------------------------------------------------------------mentioning
confidence: 48%
“…HBV infection and cirrhosis are established risk factors for HCC (8,11), and several recent studies have suggested HBV infection may also be associated with the occurrence of ICC (12,13,18,19); however, the association between cirrhosis and the pathogenesis/prognosis of ICC remains unknown. The present study confirmed the earlier observation that cirrhosis is prevalent among patients with ICC in highly endemic areas (6), as it was observed in 23.0% of our patients, which is a markedly higher percentage compared with Western (26), and 90.1% of cases with cirrhosis in the present series were seropositive for hepatitis B surface antigen, indicating HBV-related cirrhosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, ICC patients carrying HBV had a better prognosis compared with those without HBV infection (64,65). This is likely due to a lower tendency for metastasis towards the perihepatic lymph nodes and a higher rate of encapsulation in ICC patients with HBV (66,67). In addition, the immunological memory caused by a previous HBV infection may be quickly activated by the HBV-relevant ICC, promoting antitumour immunity (68,69).…”
Section: Overall Survivalmentioning
confidence: 99%